Percepção de egressos sobre a formação em Engenharia de Produção: desafios e melhorias - Vicca, Victor Santa (Universidade Federal de São Carlos, 2025)
The education system is structured to produce graduates capable of meeting a standard of professional excellence that combines solid technical-scientific training with the environmental and social responsibility inherent to the student's context and historical background. This study aims to analyze specific aspects of the education provided by a Production Engineering program at a public university in São Paulo, as well as its extracurricular activities, evaluating how these elements contribute to students' training and graduates' performance in the job market. A case study with a mixed approach was conducted using questionnaires and interviews applied to the program's graduates, revealing a positive perception of the Production Engineering training, characterized by high employability in strategic sectors and the development of interpersonal skills. However, challenges were identified, such as the need for better alignment with market demands and the strengthening of research skills. The study concludes that the program makes a significant contribution to professional trajectories but requires adjustments to more effectively integrate theory and practice.
Perception of graduates on Engineering Production education: challenges and improvements
Keywords: Engenharia de Produção; Egressos; Mercado de Trabalho; Production Engineering; Graduates; Job Market; ENGENHARIAS::ENGENHARIA DE PRODUCAO